2022
DOI: 10.3390/su14041987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Consecutive Application of Phosphorus-Enriched Biochar with Different Levels of P on Growth Performance of Maize for Two Successive Growing Seasons

Abstract: Sustainable management of phosphorus (P) is one of the burning issues in agriculture because the reported P losses, when applied in the form of mineral fertilizer, give rise to another issue of water pollution as P is considered one of the limiting nutrients for eutrophication and so results in costly water treatments. In the present study, the enrichment of biochar with mineral P fertilizer was supposed to reduce such losses from the soil. Additionally, P can also be recycled through this technique at the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…Lehmann and Joseph [35] suggested that biochar application may decrease the soil pH due to the oxidation of carboxyl groups in the biochar or increase the soil pH due to the dissolution of alkaline minerals. Wali et al [36] found that soil pH was barely affected by the addition of EB with different levels of P. Previous studies have found that biochars produced at higher temperatures are basic due to the loss of acidic functional groups [37,38]. Mobilization of microbial communities and the removal of acidic constituents and carboxylic groups from biochar have been suggested as possible reasons for the reduction of pH associated with EB addition [39].…”
Section: Discussionmentioning
confidence: 99%
“…Lehmann and Joseph [35] suggested that biochar application may decrease the soil pH due to the oxidation of carboxyl groups in the biochar or increase the soil pH due to the dissolution of alkaline minerals. Wali et al [36] found that soil pH was barely affected by the addition of EB with different levels of P. Previous studies have found that biochars produced at higher temperatures are basic due to the loss of acidic functional groups [37,38]. Mobilization of microbial communities and the removal of acidic constituents and carboxylic groups from biochar have been suggested as possible reasons for the reduction of pH associated with EB addition [39].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the aging of the biochar itself, previous studies have shown that positive effects of biochar on soil fertility can either increase over time (Kätterer et al, 2019;Jiang et al, 2022;Wali et al, 2022) or decrease over time (Olszyk et al, 2020). We were not able to identify literature that documented changes in how plants respond to biochar as the plants themselves mature.…”
Section: Does the Response Of Willows To Biochar Change During A Seco...mentioning
confidence: 94%
“…Potassium dihydrogen phosphate solution is a popular chemical used to load biochar with phosphorus via adsorption, which was investigated in the studies by Ahmad et al (2018), Wu et al (2019a), Li et al (2020a), Nardis et al (2022), Mihoub et al (2022), andArwenyo et al (2022). On the other hand, Wali et al (2020), Wali et al (2022), and Suwanree et al ( 2022) used di-ammonium phosphate as the enrichment source. Adsorption is a commonly employed technique to load biochar with phosphorus, and it often involves the use of liquid phosphorus sources.…”
Section: Phosphorus Sources For Biochar Loadingmentioning
confidence: 99%